Transition from intravenous treprostinil to enteral selexipag in an infant with pulmonary arterial hypertension. (June 2019) - Koo, Rachel; Lo, Jennifer; Bock, Matthew J.
Abstract: Selexipag is an enteral, selective prostacyclin IP receptor agonist approved for pulmonary hypertension in adults. There are few reports of its use in children and none in infants. We report the first transition of an infant (11.5 months, 8.6 kg) from intravenous treprostinil (40 ng/kg/minute) to enteral selexipag (400 mcg twice daily) with a good response and no adverse effects.